Comparison of Ni0.6Co0.4Fe2O4 and NiFe2O4 Nanoparticles for Magnetic Characteristics, Synthesized Using Co-Precipitation Method - Utari Utari; Yeni Herlina K. Dasi; Budi Purnama (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2022)
Comparison of nickel Ni0.6Co0.4Fe2O4   and NiFe2O4 were studied. The co-precipitation method was performed for the whole sample. After annealing of 600°C for 4 hours, the nanoparticles samples evaluated their structural properties by using Fourier Transform Infra-Red (FTIR) and X-Ray Diffraction (XRD). The XRD pattern confirms that the whole samples have the crystalline structure of the face-centered cubic (fcc) inverse spinel. Furthermore, the lattice and crystallite size of NiFe2O4 increased when added Co2+. The FTIR spectrum showed two prominent absorption bands, i.e., at around k of 358 cm-1 and 588 cm-1, where metals at tetrahedral and octahedral sites reflect intrinsic vibrations, respectively.  Finally, the decrease of saturated magnetization MS from 22.2 emu/g and 9.92 emu/g replacement of Co2+ cation with Ni2+.